Localization of ORC1 During the Cell Cycle in Human Leukemia Cells - Frederick D. Coffman; Mai-Ling Reyes; Monique Brown; W. Clark Lambert; Stanley Cohen (Analytical Cellular Pathology)
The interaction of the origin recognition complex (ORC) with replication origins is a critical parameter in eukaryotic replication initiation. In mammals the ORC remains bound except during mitosis, thus the localization of ORC complexes allows localization of origins. A monoclonal antibody that recognizes human ORC1 was used to localize ORC complexes in populations of human MOLT-4 cells separated by cell cycle position using centrifugal elutriation. ORC1 staining in cells in early G1 is diffuse and primarily peripheral. As the cells traverse G1, ORC1 accumulates and becomes more localized towards the center of the nucleus, however around the G1/S boundary the staining pattern changes and ORC1 appears peripheral. By mid to late S phase ORC1 immunofluorescence is again concentrated at the nuclear center. During anaphase, ORC1 staining is localized mainly in the pericentriolar regions. These findings suggest that concerted movements of origin DNA sequences in addition to the previously documented assembly and disassembly of protein complexes are an important aspect of replication initiation loci in eukaryotes.